2017
DOI: 10.1093/jpepsy/jsx078
|View full text |Cite
|
Sign up to set email alerts
|

Using Mobile-Technology-Based Ecological Momentary Assessment (EMA) Methods With Youth: A Systematic Review and Recommendations

Abstract: Ecological momentary assessment (EMA) methods are increasingly used in social and health sciences, but the feasibility and best practices for using EMA with youth are not yet clear. We conducted a systematic review of studies that used self-report EMA methods with youth; the goal was to identify common approaches and challenges to implementation and develop recommendations for future research. We examined 54 peer-reviewed papers that reported on 24 unique studies. Papers were evaluated using a standardized, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
160
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(192 citation statements)
references
References 62 publications
7
160
4
1
Order By: Relevance
“…Many EMA studies have been conducted with children and adolescents, summarized in two recent systematic reviews (Heron, Everhart, McHale, & Smyth, ; Wen, Schneider, Stone, & Spruijt‐Metz, ). Most EMA studies with children and adolescents have ranged in length from 2 to 42 days, involved two to nine survey prompts daily, used digital technology to collect self‐reports, provided monetary incentives to encourage compliance, and trained young participants to operate EMA devices and/or respond to EMA survey questions before going into the field (Heron et al, ; Wen et al, ). The use of EMA is supported with children and adolescents as young as 7 years of age, as youth of different genders, racial/ethnic groups, nationalities, socioeconomic backgrounds, and mental or physical health conditions all have effectively and compliantly participated in EMA research (Heron et al, ).…”
Section: How Is Ema Employed?mentioning
confidence: 99%
See 4 more Smart Citations
“…Many EMA studies have been conducted with children and adolescents, summarized in two recent systematic reviews (Heron, Everhart, McHale, & Smyth, ; Wen, Schneider, Stone, & Spruijt‐Metz, ). Most EMA studies with children and adolescents have ranged in length from 2 to 42 days, involved two to nine survey prompts daily, used digital technology to collect self‐reports, provided monetary incentives to encourage compliance, and trained young participants to operate EMA devices and/or respond to EMA survey questions before going into the field (Heron et al, ; Wen et al, ). The use of EMA is supported with children and adolescents as young as 7 years of age, as youth of different genders, racial/ethnic groups, nationalities, socioeconomic backgrounds, and mental or physical health conditions all have effectively and compliantly participated in EMA research (Heron et al, ).…”
Section: How Is Ema Employed?mentioning
confidence: 99%
“…Most EMA studies with children and adolescents have ranged in length from 2 to 42 days, involved two to nine survey prompts daily, used digital technology to collect self‐reports, provided monetary incentives to encourage compliance, and trained young participants to operate EMA devices and/or respond to EMA survey questions before going into the field (Heron et al, ; Wen et al, ). The use of EMA is supported with children and adolescents as young as 7 years of age, as youth of different genders, racial/ethnic groups, nationalities, socioeconomic backgrounds, and mental or physical health conditions all have effectively and compliantly participated in EMA research (Heron et al, ). Heron et al () reported average EMA compliance rates – the proportion of prompts to which participants responded – of 76% across their selected studies, which is consistent with the 80% guideline offered in EMA studies with adults (Stone & Shiffman, ).…”
Section: How Is Ema Employed?mentioning
confidence: 99%
See 3 more Smart Citations